Tea contamination by mycotoxins and azole-resistant mycobiota: the need of a One Health approach to tackle exposures - Viegas, Carla (2023)
Despite tea beneficial health effects, there is a substantial risk of tea contamination by harmful pathogens and mycotoxins. A total of 40 tea samples (17 green (raw) tea; 13 black (fermented) tea; 10 herbal infusions or white tea) were purchased from different markets located in the Lisbon district in 2020. All products were directly available to consumers either in bulk (13) and or in individual packages (27). Bacterial analysis was performed by inoculating 150 μL of samples extracts in tryptic soy agar (TSA) supplemented with 0.2 % nystatin medium for mesophilic bacteria, and in Violet Red bile agar (VRBA) medium for coliforms (Gram-negative bacteria). Fungal research was performed by spreading 150 μL of samples in malt extract agar (MEA) supplemented with 0.05 % chloramphenicol and in dichloran-glycerol agar (DG18) media. The molecular detection of the Aspergillus sections Fumigati, Nidulantes, Circumdati, and Flavi was carried out by Real-Time PCR (qPCR). Detection of mycotoxins was performed using a high-performance liquid chromatograph (HPLC) with a mass spectrometry detector. Azole resistance screening was achieved following the EUCAST guidelines. The highest counts of total bacteria (TSA) were obtained in green raw tea (81.6 %), while coliform counts (VRBA) were found in samples from black raw tea (96.2 %). The highest fungal counts were obtained in green raw tea (87.7 % MEA; 69.6 % DG18). Aspergillus sp. was the most prevalent genus in all samples on MEA (54.3 %) and on DG18 (56.2 %). In the raw tea 23 of the samples (57.5 %) presented contamination by one to five mycotoxins in the same sample. One Aspergillus section Fumigati isolate from a green tea beverage recovered from itraconazole-Sabouraud dextrose agar (SDA) medium, presented itraconazole and posaconazole E-test MICs above MIC90 values. Our findings open further discussion regarding the One-Health approach and the necessary investment in researching biological hazards and azole resistance associated with the production and consumption of tea (in particular green tea).